2016
DOI: 10.1002/jbmr.3046
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Gene Clock Regulates Bone Formation Via PDIA3

Abstract: The expression patterns of clock-controlled genes (ccgs) are regulated by circadian rhythm, which is a major regulatory and physiological mechanism tied to the solar day. Disruptions in circadian rhythm contribute to the development of cardiovascular diseases, cancer, metabolic syndromes, and aging. It has been reported that bone remodeling is also regulated by circadian rhythm. However, the molecular mechanism by which the circadian gene Clock regulates bone remodeling has yet to be elucidated. Here, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 41 publications
(51 reference statements)
0
65
0
Order By: Relevance
“…The importance of rhythm in clock gene expression for bone has been established previously by the presence of a bone phenotype in clock gene knockout mice. Mice lacking Clock or Bmal1 have a reduced bone mass, 21,24 while Per1/2 and Cry1/2 double knockout mice have an increased bone mass, 20 indicating involvement of clock genes in bone turnover. This is supported by our data demonstrating a rhythm in the expression of various bone-related genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of rhythm in clock gene expression for bone has been established previously by the presence of a bone phenotype in clock gene knockout mice. Mice lacking Clock or Bmal1 have a reduced bone mass, 21,24 while Per1/2 and Cry1/2 double knockout mice have an increased bone mass, 20 indicating involvement of clock genes in bone turnover. This is supported by our data demonstrating a rhythm in the expression of various bone-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…14 Osteoblasts can communicate with osteoclasts by excreting receptor activator of nuclear factor κ-B ligand (RANKL), which binds to its receptor RANK on osteoclasts. 19 Furthermore, genetic disruption of clock genes affects the bone phenotype in mice, [20][21][22][23][24] suggesting a causal link between circadian physiology and bone health. Another protein secreted by osteoblasts is osteoprotegerin (OPG), which binds to RANKL and prevents it from interacting with RANK, thus preventing the bone from excessive resorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 20 top diurnally classified genes, we found that 50% of those genes were previously correlated with circadian behavior (Table S1), such as DDIT4 9 (Fig. 2b), SMAP2 26 , and PDIA3 36 . However, only 101/366 (27.6%) of these genes are detected as diurnal at the whole population level (FDR < 0.05, multiple comparison corrected), suggesting there may be many more diurnally-varying genes than previously discovered.…”
Section: Discussionmentioning
confidence: 95%
“…In the U.S., 89% of adults who have diabetes are also overweight or have obesity 18 . Obesity disrupts breathing that leads to sleep apnea and disordered sleep/wake cycle, which further causes the circadian related diseases and promotes virus infection [19][20][21][22][23][24][25] . Obesity also affects the mitochondrial structure and function 26 , which further leads to physiological dysfunction and the related diseases 27,28 .…”
Section: Discussionmentioning
confidence: 99%